Pelatihan Manajemen Keuangan Bagi Usaha Mikro Kecil Menengah Sidayu Gresik - Akhmad Wasiur Rizqi; Moch Nuruddin; Dhidu Usrin Yadani; M.Syafiqul Ma’arif; Harunur Rosyid (Pusat Riset dan Inovasi Nasional, 2024)
Financial management training with a service object intended for MSME business actors who are members of the MSME association of Sidayu district located in Mriyunan Village, Sidayu District, Gresik Regency. This community service is a form of campus participation, especially the Department of Industrial Engineering Muhammadiyah Gresik in improving the ability of local resources, namely MSMEs. The purpose of community service activities is to provide education to Sidayu MSME actors to pay attention to the importance of financial management in business management. Sidayu MSME actors by knowing the financial attribute factors in the business process can control by minimizing and eliminating losses that occur so that the business management process is better and increases income